Economic Order Quantity Determination : A Case Study Of ABC Pharmacy - Sriyom, Kulaya (Journal of Science and Technology Songkhla Rajabhat University, 2021)
This research is a study on the management of the inventory of pharmaceutical stores. The study aims to study the quantity and cost list of pharmacokinetic outlets. 60 study of warehouse management by ABC Analysis, appropriate order quantity (EOQ) and reordering point (ROP) of 60 drug items.Then the numerical data is calculated according to the ABC Analysis method. The results showed that groupings based on the value of pharmaceutical items showed that Group A totaled 50 items with a total value of 16,168,550 baht, representing 65.97% of the total value.There are 4 items with a total value of 3,554,450 Baht, representing 14.50% of the total value. (EOQ) is used to calculate the appropriate order quantity so that it can be used as a model for proper warehouse management.